2013
DOI: 10.4274/tjh.2012.0092
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effects of a Blood Stopper Agent (Ankaferd Blood Stopper) on Bone Surfaces

Abstract: Objective: This study aims to experimentally investigate the efficiency of Ankaferd Blood Stopper (ABS) on early and long-term bone healing and its effects on bone surfaces. Materials and Methods: Thirty adult male Wistar albino rats were used in the study. These rats were randomly divided into three groups, and bilaterally bone defects were created in the femur of each rat. A 3.0-mm-deep monocortical circular defect was created with a 3.0 mm diameter trephine drill on the proximal part of the femur, and 0.05 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…Consistent with our results, application of the ABS has been shown to decrease inflammation and necrosis, while increasing new bone formation during the early bone healing period . Likewise, in another experimental study, the findings suggested that ABS had an accelerator effect on short‐term bone healing . ABS has also been shown to exert anti‐infective and healing modulator properties that are also crucial periodontal interventions .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our results, application of the ABS has been shown to decrease inflammation and necrosis, while increasing new bone formation during the early bone healing period . Likewise, in another experimental study, the findings suggested that ABS had an accelerator effect on short‐term bone healing . ABS has also been shown to exert anti‐infective and healing modulator properties that are also crucial periodontal interventions .…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the direct usage of ABS in the management of hemorrhagic disorders, off‐label applications have been tested . Such applications demonstrated that ABS could enhance wound healing, infection control, early stage bone tissue healing and formation . These studies demonstrated that the pro‐regenerative and pro‐angiogenic properties of the ABS could be beneficial for a wide spectrum of clinical applications, including the restoration of hard and soft tissues.…”
mentioning
confidence: 99%
“…All of these plants show their effects on the endothelium, blood cells, angiogenesis, cellular proliferation, vascular dynamics, and mediators. There are many studies reporting that ABS can be used as a hemostatic agent to control hemorrhage after dental extraction, surgical operation, subgingival curettage, and periodontal plastic surgery (24)(25)(26). Studies have also been conducted on the effect of ABS on bone and soft tissue wound healing (26).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that bone defects treated with ABS were free of inflammation, which is probably related to the anti-inflammatory activity of ABS. Şimşek et al [32] also studied on rat femoral defect models for the effects of ABS on bone defects. They concluded that ABS has an acceleratory effect on short-term bone healing process; however, its effect on long-term bone healing process is insignificant.…”
Section: Discussionmentioning
confidence: 99%